The Author’s Factor in the Hermeneutic Process - Мусиенко, Валентина Павловна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article deals with author’s factor in the process of the interpretation of the text.Domination of the author's position is assessed through the prism of subjectivism and intentionalism. The dependence of the influence of the author's personality in the interpretation of the text on it’s type is noticed. Future prospects for a comparative study of the author's role in unfolding texts with a common subject of speech are outlined. The most important coordinates for fixing the author's position regarding to the content of the statement are determined and demonstrated on the texts: the nature of the presence, the degree of objectivity, the evaluation, the level of evidence.Two types of author’s presence are distinguished: explicit or implicit. The degree of author's objectivity is presented in the form of a scale: subjectivity, conventionality, objectivity, conditional objectivity (lack of markers), taking into account the interests pursued. The author's assessment of the subject of speech is characterized in the parameters well – normally – badly, the determination of its explication is indicated by the type of discourse. It is noted that the category of evidence of the author's position, the most significant in the scientific and political discourse, is on the border between the author's and reader's position: it is programmed by the author, but ultimately is in the power of the recipient.